339 Influence of SEEG on Temporal Lobectomy. (1st April 2022) - Kondylis, Efstathios; Hsieh, Jason K.; Sundar, Swetha J.; Sarmey, Nehaw; Schmidt, Eric; Rammo, Richard; Bulacio, Juan; Jehi, Lara; Bingaman, William E.
Abstract : INTRODUCTION: Seizure outcomes after surgical resection in temporal lobe epilepsy (TLE) are historically better in the presence of a discrete MRI lesion, as the surgical hypothesis is better informed by imaging. The role of intracranial monitoring via stereotactic electroencephalography vs. proceeding directly to surgery in this patient population remains under debate. METHODS: SEEG usage trends were investigated for 391 consecutive patients who had temporal lobectomy performed from 2015 to 2020. Correlation with Engel scores at 1 year post-op was performed using chi-square for 259 patients in whom this data was available. RESULTS: Sparing of mesial structures was more common in patients who had SEEG (35% vs 20%, p < 0.01). There was a nonsignificant trend towards better outcomes in patients who did not have SEEG (63.5% Engel 1 vs 50.5%, p < 0.55). MRI abnormalities were significantly more prevalent in the cohort that underwent SEEG (92% vs. 58%, p < 0.001), and there was no significant association between the presence of MRI abnormality and outcome (p = 0.59). CONCLUSION: We found no statistically significant difference in seizure freedom in patients who undergo temporal lobectomy with SEEG in the presurgical workup. This likely results from SEEG being used when the surgical hypothesis is difficult to formulate, reflected by the increased prevalence of distinct imaging abnormalities in the non-SEEG cohort. Thus it seems that the use of SEEG helps close the gap in outcomes for patients with non-lesional temporal lobe epilepsy. There was no difference in outcomes associated with the decision to spare mesial structures, indicating this effect likely stems from patient selection for surgery. Our future work will look into the connection between SEEG and volumes of surgical resection.